Comparison of the Eggs and Cocoons Quality of Some Mulberry Silkworm Hybrid Bombyx mori L. - Lincah Andadari; Yetti Heryati; Retno Agustarini; Herman Sari; Eyet Mulyati (Jurnal Sylva Lestari, 2023)
Sericulture is one of the non-timber forest products (NTFPs) that can help Indonesians live better lives and support environmental improvement. Silk, as a product of sericulture, is one of the five NTFPs that Indonesia has identified as having the ability to boost the nation’s economy and alleviate poverty. However, there are several issues with the development of silk in Indonesia, chiefly issues with the quality of silkworm seedlings and low cocoon yield. Crossbreeding is one method used to boost egg output. This study aimed to evaluate the eggs and cocoons produced by various silkworm (Bombyx mori L.) crosses. The Pustarhut Laboratory hosted the research from May to August 2022. Twelve treatments were employed in the form of crosses using the Randomized Block Design (RBD) method, and each treatment applied three replicates. Overall, the findings demonstrated that the CE cross ((919 x 927) x (804 x p208)) produced eggs (652 eggs) and cocoons of higher quality than other crossings. However, although the egg numbers of CF cross ((919 × 927) × (p208 × 804)) and FC cross ((p208 × 804) × (919 × 927)) produced 622 and 631 eggs, respectively and were significantly different from CE cross, they still produced egg numbers above 600. In addition, they produced cocoon quality that was not significantly different from CE cross. All finding indicates that silkworms from CE, CF, and FC crosses can be used as an alternative to superior silkworm breeding to increase the productivity of silkworm rearing in Indonesia. Keywords: Bombyx mori, cocoon quality, double-cross, seed quality